Physico-chemical characterization of gas-condensate deposits of the eastern region of Ukraine - Луганова, Т.О.; Михайлюк, Ю.В.; Москалик, А.А.; Походенько, О.С. (Proceedings of National Aviation University (archive), 2009)
The general review of hydrocarbon's potential of East region of Ukraine. Physical and chemical characteristic of basic gaseous condensate deposits.